2012
DOI: 10.1107/s0021889812041039
|View full text |Cite
|
Sign up to set email alerts
|

Diffraction/scattering computed tomography for three-dimensional characterization of multi-phase crystalline and amorphous materials

Abstract: International audienceThe three-dimensional characterization method described herein is based on diffraction and scattering techniques combined with tomography and uses the variation of these signals to reconstruct a two-dimensional/three-dimensional structural image. To emphasize the capability of the method in discriminating between different poorly ordered phases, it is named diffraction/scattering computed tomography (DSCT). This combination not only allows structural imaging but also yields an enhancement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
45
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 62 publications
0
45
0
Order By: Relevance
“…176 It has been applied recently with a reasonable speed (acquisition of a slice in 20 min) for the study of structural change during high temperature modification of catalysts. 177 Alvarez-Murga et al 178 reviewed some recent results on diffraction/scattering computed tomography. They showed that the method yields an enhancement in the detection of the weak signals coming from minor phases.…”
Section: Chemical Tomographymentioning
confidence: 99%
“…176 It has been applied recently with a reasonable speed (acquisition of a slice in 20 min) for the study of structural change during high temperature modification of catalysts. 177 Alvarez-Murga et al 178 reviewed some recent results on diffraction/scattering computed tomography. They showed that the method yields an enhancement in the detection of the weak signals coming from minor phases.…”
Section: Chemical Tomographymentioning
confidence: 99%
“…The RDF can be determined from X-ray and neutron diffraction data [1][2] and has been widely applied to investigate amorphous materials such as organic solids [3], liquids [4] [5], metallic glasses [6], phase-change memory materials [7] and nanoscaled energy storage materials [8] [9]. Jacques et al combined RDF analysis with X-ray diffraction computed tomography (XRD-CT) [10] for spatially resolved RDF analysis of heterogeneous structures, where structural features around tens of micrometers could be resolved [11].…”
Section: Introductionmentioning
confidence: 99%
“…The beam size and the corresponding spatial resolution should be therefore adapted to the grain size of the specimen, fulfilling the requirement that the number of crystallites in the irradiated volume is large. In spite of this constraint remarkable spatial resolutions of the order of 100 nm could be obtained for nanograined materials (Á lvarez-Murga et al, 2012). An interesting application is given by Stock & Almer (2012), by reconstructing the structure of an SiC-monofilament-reinforced Al-matrix composite.…”
mentioning
confidence: 99%
“…Diffraction/scattering computed tomography (DSCT), presented by Á lvarez- Murga et al (2012), also uses a pencil beam which, however, is monochromatic. DSCT is well adapted for differentiating among multi-phase compounds with similar densities and compositions by exploiting their structural and/or microstructural properties.…”
mentioning
confidence: 99%